Auch Henker sterben - Donlevy, Brian 1901-1972; Brennan, Walter 1894-1974; Lee, Anna 1913-2004 (Suhrkamp, 2011)
After the Nazi administrator of Czechoslovakia is shot, his assassin tries to elude the Gestapo and struggles with his impulse to give himself up as hostages are executed. (www.imdb.com)
Sonstiges: Kapiteleinteilung, Booklet
FSK ab 16 Jahren freigegeben
USA 1943
Keywords: DVD-Video